PENETAPAN ANGKA STANDARD FAKTOR EKSPLOITASI HUTAN ALAM DAN POTENSI LIMBAH PEMANENAN KAYU SUB REGION PROVINSI KALIMANTAN TENGAH - Soenarno; Yuniawati; Dulsalam; Sona Suhartana (BRIN Publishing, 2021)
Currently, timber harvesting activities in natural forests are more efficient with reduced impact logging (RIL). More efficientwood harvesting will reduce waste, which increases the standardization of exploitation factors (FE). Ironically, until now, theFE standard set by the Ministry of Environment and Forestry is still based on conventional wood harvesting methods, which is0.7. The sub-region of Central Kalimantan Province has a major role in contributing to production of natural forest logs, bothregionally on the island of Kalimantan by 61.5% and nationally by 29.7%. Still, the amount of wood harvesting waste is notknown with the standardized exploitation factor. This study aimed to obtain a standard number of exploitation factors fortimber harvesting activities in natural production forests in the sub-regional province of Central Kalimantan. The research wasconducted by initially selecting purposively logging companies with Sustainable Production Forest Management (PHPL)mandatory and voluntary certificates. The study was conducted in five of Forest Utilization Business License (PBPH) withPHPL mandatory certified and voluntary certificates. The results showed that the potential for logging waste due to stem divisionin felling site is an average of 0.919 m3/tree and the amount of logging waste due to testing and measurement at the TPn is onaverage 0.093 m3/tree. The FE score ranged from 0.80-0.85 with an average of 0.82. Factors that influenced the FE coefficientinclude the skill of the logger and management policy of PBPH and the diameter of the tree felled.